2010
DOI: 10.1007/s12011-010-8890-z
|View full text |Cite
|
Sign up to set email alerts
|

Excess Dietary Vanadium Induces the Changes of Subsets and Proliferation of Splenic T Cells in Broilers

Abstract: The purpose of this 42-day study was to investigate the effects of dietary excess vanadium on immune function by determining changes of the subsets and proliferation function of splenic T cells. Four hundred twenty 1-day-old avian broilers were divided into six groups and fed on a corn-soybean basal diet as control diet or the same diet amended to contain 5, 15, 30, 45, and 60 ppm of vanadium supplied as ammonium metavanadate. When compared with those of the control group, the percentage of CD3+, CD3+CD4+, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…CD 4 + T cells concentrate in the inter-follicular areas, and both CD 3 + and CD 8 + T cells distribute in the lamina propria and epithelium [17]. In the present study, the percentages of CD 3 + , CD 3 + CD 8 + , and CD 3 + CD 4 + in cecal tonsil were decreased in 45 and 60 mg/kg groups and increased in 5 mg/kg group, which were consistent with the results of our recent studies [18,19]. The results showed that the population and biological function of mature T cells were affected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CD 4 + T cells concentrate in the inter-follicular areas, and both CD 3 + and CD 8 + T cells distribute in the lamina propria and epithelium [17]. In the present study, the percentages of CD 3 + , CD 3 + CD 8 + , and CD 3 + CD 4 + in cecal tonsil were decreased in 45 and 60 mg/kg groups and increased in 5 mg/kg group, which were consistent with the results of our recent studies [18,19]. The results showed that the population and biological function of mature T cells were affected.…”
Section: Discussionsupporting
confidence: 93%
“…The composition of mature T cells decides the biological function of mature T cells and is related to the cellular immune function of the body. The results of our recent studies show that dietary vanadium in excess of 30 mg/kg can reduce the splenic and peripheral blood T cell population and proliferation and the serum interleukin-2 (IL-2) contents [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Other biological functions of vanadium and vanadium compounds as anti-tumor drugs, anti-parasitic agents and their estrogenic actions, reflecting recently medicinal applications of this element, and their availability and safety for clinical use have also been described recently [6]. In addition, our studies show that excessive vanadium strongly negatively affects the normal cellular immunity [7][8][9][10].…”
Section: Introductionsupporting
confidence: 57%
“…Because of that, secretion of IL-2 and IL-6 is affected ( Figure 3 ). Furthermore, ammonium metavanadate (NH 4 VO 3 ) ( Table 1 ) inhibits the proliferation activity of CD3 + , CD3 + CD4 + , and CD3 + CD8 + splenic T cells and depresses their activity in broilers [ 19 ]. According to this study, vanadium can affect the percentage of splenic T cell subsets, the proliferation of splenic T cells, and serum IL-2 and IL-6 content.…”
Section: Regulation Of T Cell Signalingmentioning
confidence: 99%